Cytolytic toxin production by Staphylococcus aureus is dependent upon the activity of the protoheme IX farnesyltransferase. Issue 1 (December 2017) - Stevens, Emily; Laabei, Maisem; Gardner, Stewart; Somerville, Greg; Massey, Ruth
Abstract Staphylococcus aureus is a medically important pathogen with an abundance of virulence factors that are necessary for survival within a host, including the production of cytolytic toxins. The regulation of toxin production is mediated by the Agr quorum sensing system, and a poorly defined post-exponential growth phase signal independent of Agr. As part of a recent genome wide association study (GWAS) to identify novel loci that alter the expression of cytolytic toxins, a polymorphism in thecyoE gene, which encodes a protoheme IX farnesyltransferase, was identified. This enzyme is essential for processing heme into the electron transport chain for use as an electron acceptor. Interestingly, without this enzymeS. aureus were repressed in their ability to secrete cytolytic toxins, and this appears to be mediated through repression of the Agr quorum sensing system. We hypothesize that the loss of electron transport is inducing feedback inhibition of metabolic capabilities that suppress the TCA cycle, and that this coupled with decreased RNAIII transcription prevents synthesis of cytolytic toxins.